O contraste entre oclusivas alveolares e velares em dados típicos de fala: análises acústica e ultrassonográfica - Melo, Roberta Michelon; Mota, Helena Bolli; Berti, Larissa Cristina (FapUNIFESP (SciELO), 2017)
Purpose: This study used acoustic and articulatory analyses to characterize the contrast between alveolar and velar stops with typical speech data, comparing the parameters (acoustic and articulatory) of adults and children with typical speech development. Methods: The sample consisted of 20 adults and 15 children with typical speech development. The analyzed corpus was organized through five repetitions of each target-word (/'kap ə/, /'tapə/, /'galo/ e /'daɾə/). These words were inserted into a carrier phrase and the participant was asked to name them spontaneously. Simultaneous audio and video data were recorded (tongue ultrasound images). The data was submitted to acoustic analyses (voice onset time; spectral peak and burst spectral moments; vowel/consonant transition and relative duration measures) and articulatory analyses (proportion of significant axes of the anterior and posterior tongue regions and description of tongue curves). Results: Acoustic and articulatory parameters were effective to indicate the contrast between alveolar and velar stops, mainly in the adult group. Both speech analyses showed statistically significant differences between the two groups. Conclusion: The acoustic and articulatory parameters provided signals to characterize the phonic contrast of speech. One of the main findings in the comparison between adult and child speech was evidence of articulatory refinement/maturation even after the period of segment acquisition.
The contrast between alveolar and velar stops with typical speech data: acoustic and articulatory analyses